La política de dividendos de las empresas españolas: un ajuste parcial al objetivo de reparto. - López de Foronda, Óscar; Díez Esteban, José María (Cuadernos de Estudios Empresariales, 2001)
The objective of this paper is to verify whether the management of the firm focuses its dividends policy towards the uxaintenance of a targel payout ratio as stated by the Lintner s model or the economie and financial situation of the firm leads to a partial adjustment of this ratio. Obtained results let us assure that the firms partially adjust their target payout ratio depending on their economic and financial situation and their finance and investment policies. To summarise, we conclude that the key points of the agency theory are very adequate to solve the dividends puzzle and to evaluate and to elaborate the organizations sharing policies. 141 La política de dividendos... José María Díez Esteban y Óscar López de Foronda Pérez 1.